Improving tribological properties of P91 steels through carburizing process. (2020) - Manjith Srinivas, K.; Bharath, S.; Krishna Chaitanya, P.N.V.; Pramod, M.; Subbiah, Ram
Abstract: The wear conduct of P91 steel has been researched under a dry sliding contact at consistent load. It was discovered that Carburizing was successful in improving the wear conduct of P91 steel material. A low temperature carburizing was completed for three distinct examples at an hour, an hour and a half and 120 min. Unnitrided austenitic treated steel was utilized as a source of perspective material and experienced wear test for comparision with nitride examples. Wear tests were conducted at 1000 rpm with an applied load of 50 N to examine the wear loss and volume wear loss of the material. The nitrided samples uncovers that hard nitride layers are formed which improves the surface hardness. Miniaturized scale hardness estimations uncovered a huge increment in hardness after treatment. The layers were further by checking electron magnifying instrument investigation.